Lead complications after cardiac surgery in patients with cardiac implantable electronic devices. (26th May 2022) - Frausing, Maria Hee Jung Park; Nielsen, Jens Cosedis; Johansen, Jens Brock; Jørgensen, Ole Dan; Kristensen, Jens; Olsen, Thomas; Gerdes, Christian; Kronborg, Mads Brix
Abstract: OBJECTIVES: Manipulation of the heart during cardiac surgery in patients with cardiac implantable electronic devices (CIEDs) may result in lead damage or displacement, but whether cardiac surgery truly infers an excess risk of lead failure is not known. The objective of this study was to examine the risk of lead complications after cardiac surgery in patients with CIEDs. METHODS: We conducted a nationwide nested case–control study. The source population comprised all Danish patients ≥18 of age who underwent a de novo CIED implantation during 1998–2017. For inclusion, patients had to be alive and event free 6 months after implantation. Cases were matched 1:30 to controls on time, age, sex, and device type using risk set sampling. We used conditional logistic regression to estimate incidence rate ratios (IRRs) for the association between cardiac surgery and lead-related reoperation. RESULTS: Our final population consisted of 67 621 patients. We identified 1437 (2.1%) incident cases of lead-related reoperations and 42 698 controls. Risk of lead complications was highest within 6 months of cardiac surgery [IRR 9.7, 95% confidence interval (CI) 6.3–14.8, adjusted IRR 9.6, 95% CI 6.2–14.7], and at 1 year, the relative risk of lead-related reoperation was close to unity (adjusted IRR 1.2, 95% CI 0.8–1.7). CONCLUSIONS: Cardiac surgery was associated with a considerable risk of lead complications in patients with de novo CIEDs. Abstract : An improved understanding of the pathogenic mechanisms underlying cardiac arrhythmias and concurrent evolving technologies have expanded indications for cardiac implantable electronic device (CIED) therapy over the past decades [1].